Novel management of ovarian vein thrombosis: A case report - Joseph Naoum; Amani Mohsen; Jihad Daher; Toufic Eid (Saudi Pharmaceutical Journal)
Ovarian vein thrombosis (OVT) is a rare serious diagnosis especially if extending to inferior vein cava (IVC). We present a case of 36-year- old female who was diagnosed with right OVT reaching the inferior vein cava following a supra-cervical hysterectomy that was performed in the postpartum period due to excessive bleeding from uterine fibroids. Using the new generation anti-coagulant “rivaroxaban” for six months followed by maintenance regimen of aspirin and sulodexide, complete resolution of the clot was noticed without any adverse event while using this regimen. This is the first OVT case which is completely treated with rivaroxaban without any adjunct invasive modality. Keywords: Rivaroxaban, Ovarian vein thrombosis